Deep venous structures distortion in spontaneous intracranial hypotension as an explanation for altered level of consciousness. (24th September 2013) - Ajlan, Abdulrazag M; Al-Jehani, Hosam; Torres, Carlos; Marcoux, Judith
Abstract : Spontaneous intracranial hypotension (SIH) is a syndrome of low pressure headache associated with low CSF pressure. The condition is generally considered benign but extreme cases of SIH can lead to changes in the level of consciousness. We describe a case in which alteration in the level of consciousness was prolonged and severe, and could not be explained solely by the presence of subdural collections. MRI of the brain showed evidence of impaired venous flow secondary to brain sagging causing distortion of deep venous structures.